At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

What is the inverse of the function g(x)=-3(x + 6)?
Please help me ASAP


Sagot :

Answer:

Inverse g(x) = -x/3-6

Step-by-step explanation:

To understand this just think g(x) as y so

we got y= -3(x+6) after that we change the minus three to left

so we got -y/3 because -3 is multiply. After that plus 6 came and become minus 6.

After all,you have to replace x in y place.

y = -3(x +6)

-y/3 = x +6

-y/3 -6 = x

-x/3 -6 = g(x)